A high-strength antistatic polyoxymethylene composite material and preparation method thereof

By introducing surface functionalized MWCNTs and coupling agents into polyformaldehyde, the problem of difficult dissipation of electrostatic charge of polyformaldehyde materials is solved, the high-strength antistatic properties and mechanical properties are improved, the foreign technology monopoly has been broken, and the development of domestic high-performance antistatic polyformaldehyde materials has been promoted.

CN119752095APending Publication Date: 2025-04-04CHONGQING YUNTIANHUA TIANJUXINCAI CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510003273.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

Polyformaldehyde materials have difficulty dissipating due to high resistivity, which may cause air strike discharge, affecting the operation of equipment and pose safety hazards. In addition, there is a lack of independent intellectual property rights for high-performance anti-static polyformaldehyde materials in China.

Method used

Surface-functionalized multi-walled carbon nanotubes (MWCNTs) were used as conductive fillers, and p-nitrophenyl was grafted on the surface of MWCNTs by modification method, and the interface bonding between MWCNTs and polyformaldehyde was improved by combining coupling agents to prepare high-strength anti-static polyformaldehyde composites.

Benefits of technology

It significantly reduces the surface resistivity of polyformaldehyde, improves the antistatic properties, and enhances the mechanical properties of composite materials, such as tensile strength and modulus, breaks foreign technical barriers, and realizes domestic production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005226081020000081
    Figure BDA0005226081020000081
  • Figure BDA0005226081020000091
    Figure BDA0005226081020000091
Patent Text Reader

Abstract

The invention relates to the technical field of polyoxymethylene composite materials, and discloses a high-strength antistatic polyoxymethylene composite material and a preparation method thereof. The composite material comprises 95 to 99.8 parts of polyoxymethylene, 0.2 to 5 parts of surface functionalized MWCNTs, 0.05 to 0.5 parts of antioxidant, 0.01 to 0.1 parts of formaldehyde absorber, 0.05 to 0.5 parts of nucleating agent, 0.05 to 0.2 parts of lubricant, and 0.2 to 2 parts of coupling agent. The present invention uses diazonium salt to perform surface functionalization on MWCNTs, so that the MWCNTs can be evenly distributed in the polyoxymethylene matrix to form a conductive network, so that the composite material has good antistatic properties. At the same time, thanks to the synergistic interface improvement effect of the MWCNTs surface functionalization and the coupling agent, the mechanical properties such as strength of the MWCNT / POM composite material are significantly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polyoxymethylene composite materials, and in particular to a high-strength antistatic polyoxymethylene composite material and a preparation method thereof. Background Art

[0002] Polyoxymethylene (POM), due to its unique molecular structure and excellent mechanical properties, has become an indispensable and important material in modern industry. Its regular molecular structure gives it the characteristics of high cohesive energy and high crystallinity, and thus exhibits a series of superior mechanical properties such as high strength, high rigidity, wear resistance, creep resistance, corrosion resistance, and fatigue resistance. In addition, its good processing performance has enabled polyoxymethylene to successfully replace some metal materials in many fields such as electronic appliances, precision instruments, and automobile manufacturing, and is widely used in various complex working conditions. However, despite its many advantages, polyoxymethylene, as a highly insulating polymer material, also faces a significant problem-high resistivity. This characteristic makes it easy for polyoxymethylene to accumulate a large amount of electrostatic charge during processing and use, and these charges are difficult to dissipate naturally. When the electrostatic potential is too high, it may cause air strike discharge, which not only affects the normal operation of the equipment, but also poses certain safety hazards. This undoubtedly poses a serious limitation to its processing and use performance, and has become a major bottleneck restricting the wider application of polyoxymethylene.

[0003] In order to solve the above problems, reducing the resistivity of polyoxymethylene and improving its antistatic ability have become the key. At present, common methods include adding antistatic agents to inhibit charge generation, or introducing conductive agents to accelerate charge leakage. However, since polyoxymethylene itself has poor thermal stability and high crystallinity, most antistatic agents are prone to decomposition or poor compatibility when blended with it. Therefore, finding an antistatic additive that will not cause polyoxymethylene decomposition and is well compatible with it, and developing corresponding processing technology to ensure that the modification process proceeds smoothly and can achieve the ideal antistatic effect has become a technical problem that needs to be solved urgently.

[0004] Globally, only a few internationally renowned companies have mastered mature antistatic polyoxymethylene production technology, such as DuPont, Polyplastics Co., Ltd., Korea Engineering Plastics Co., Ltd., etc. The antistatic products of these companies almost monopolize the domestic market. In contrast, domestic research on antistatic modification of polyoxymethylene is still in its infancy, mainly concentrated at the level of individual companies and university laboratories, and has not yet formed large-scale production capacity. Faced with this situation, it is urgent to strengthen independent innovation, break the technical barriers of foreign companies, and develop high-performance antistatic polyoxymethylene materials with independent intellectual property rights, so as to promote the transfer of the domestic polyoxymethylene industry to the high-end market and enhance the core competitiveness of my country's manufacturing industry. Summary of the invention

[0005] The present invention is intended to provide a high-strength antistatic polyoxymethylene composite material and a preparation method thereof, and aims to develop a high-strength antistatic polyoxymethylene through technological innovation and break through foreign technological barriers.

[0006] To achieve the above-mentioned purpose, the present invention adopts the following technical scheme: a high-strength antistatic polyoxymethylene composite material, which comprises, by weight, 95 to 99.8 parts of polyoxymethylene, 0.2 to 5 parts of surface functionalized MWCNTs, 0.05 to 0.5 parts of antioxidants, 0.01 to 0.1 parts of formaldehyde absorbers, 0.05 to 0.5 parts of nucleating agents, 0.05 to 0.2 parts of lubricants, and 0.2 to 2 parts of coupling agents.

[0007] Preferably, as an improvement, the weight parts of each raw material are 97-99 parts of polyoxymethylene, 1-3 parts of surface functionalized MWCNTs, 0.4 parts of antioxidant, 0.05 parts of formaldehyde absorbent, 0.3 parts of nucleating agent, 0.15 parts of lubricant and 1.0 parts of coupling agent.

[0008] Preferably, as an improvement, the modification method of the surface functionalized MWCNTs is: grafting p-nitrophenyl on the surface of the multi-walled carbon nanotubes.

[0009] Preferably, as an improvement, the modification method of surface functionalized MWCNTs comprises the following steps:

[0010] S1: Add p-nitroaniline and hydrochloric acid to deoxygenated water, stir to dissolve and then cool;

[0011] S2: dissolving sodium nitrite in desalted water, and then quickly adding it to the p-nitroaniline precipitate, and reacting under stirring; filtering after the reaction is completed, and the filtrate is p-nitroaniline diazonium salt;

[0012] S3: adding a surfactant to the MWCNTs, adding the mixture to desalted water, stirring, and adding p-nitroaniline diazonium salt; filtering after the reaction is completed to obtain surface functionalized MWCNTs;

[0013] S4: washing the surface functionalized MWCNTs with desalted water to remove residual diazonium salt, and then freeze-drying to obtain dry and dispersed surface functionalized MWCNTs.

[0014] Preferably, as an improvement, the antioxidant includes at least one of [methyl-β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] pentaerythritol ester, triethylene glycol bis-3-(3-tert-butyl-4-hydroxy-5-toluene phenyl) acrylate), 2,4,6-tri-tert-butylphenol, 2,6-di-tert-butyl-p-cresol, 2,6-di-tert-butyl-4-ethylphenol, and β-(4-hydroxy-3,5-di-tert-butylphenyl) propionate.

[0015] Preferably, as an improvement, the formaldehyde absorber includes at least one of sebacic acid dihydrazide, 1,3-diamino-2-propanol, dicyandiamide, melamine and triethanolamine; the nucleating agent includes at least one of di(4-tert-butyl-benzoic acid)aluminum hydroxide, aromatic amide compounds, di(p-methylbenzylidene)sorbitol, MDBS, di(p-chlorobenzylidene)sorbitol, DBS and di(3,4-dimethylbenzylidene)sorbitol.

[0016] Preferably, as an improvement, the lubricant includes at least one of paraffin, N,N'-ethylene bisstearamide, stearic acid, and butyl stearate; the coupling agent includes at least one of γ-(methacryloyloxy)propyl trimethoxysilane, γ-glycidyloxypropyl trimethoxysilane, γ-aminopropyl triethoxysilane, tri[(dioctyloxy)phosphoryl] isopropyl titanate, and diisostearoyl titanate; the lubricant includes at least one of liquid paraffin, polyethylene wax, butyl stearate, and polymethylphenylsiloxane.

[0017] Preferably, as an improvement, a method for preparing a high-strength antistatic polyoxymethylene composite material comprises the following steps:

[0018] Step 1: coating a coupling agent on the surface of polyformaldehyde pellets, and baking to obtain polyformaldehyde coated with the coupling agent;

[0019] Step 2: Mix the coupling agent-coated polyoxymethylene, antioxidant, formaldehyde absorbent, lubricant and surface-functionalized MWCNTs, and then add them into a high-speed mixer and mix them evenly to obtain a composite material raw material;

[0020] Step 3: Extruding and granulating the composite material uniformly mixed in step 2 to obtain a MWCNT / POM composite material.

[0021] Preferably, as an improvement, in step three, the composite material raw material is added to the main feed port of the twin-screw extruder, and wet MWCNT / POM composite material pellets are obtained through extrusion, cooling, drawing and granulation, and then the MWCNT / POM composite material is obtained through drying.

[0022] Preferably, as an improvement, in step three, the temperatures of each section from the main feed port to the die of the twin-screw extruder are set to 150°C, 190°C, 200°C, 205°C, 210°C, and 220°C, respectively, and the main engine frequency is 20 to 50 Hz.

[0023] The principles and advantages of this solution are:

[0024] (1) The preparation method of this technical solution uses multi-walled carbon nanotubes (MWCNTs) as conductive fillers. MWCNTs are an inorganic nanofiller that does not promote the decomposition of polyoxymethylene at high temperatures.

[0025] (2) Through the functionalization treatment of the surface of MWCNTs, p-nitrophenyl is grafted on its surface, which greatly reduces the van der Waal force between carbon nanotubes, thus having good dispersibility. When MWCNTs are used to fill and modify POM, MWCNTs can be evenly distributed in the POM matrix to form a conductive network, which sharply reduces the surface resistivity of the MWCNT / POM composite material and obtains antistatic properties.

[0026] (3) Another beneficial effect of the functionalization treatment of the MWCNTs surface is that the MWCNTs surface changes from inert to active, which is beneficial to enhance the interface between MWCNTs and POM. Furthermore, a coupling agent is used to improve the interfacial bonding between MWCNTs and the POM matrix. The synergistic effect of the two effectively increases the interfacial bonding strength between MWCNTs and the POM matrix, thereby significantly improving the mechanical properties of the MWCNT / POM composite material.

[0027] (4) This technical solution uses MWCNTs as conductive fillers and provides a filling modification process that is compatible with it, successfully achieving antistatic modification of polyoxymethylene (surface resistivity 8.5×10 6Ω). Since MWCNTs have excellent properties such as high strength, high modulus, and low density, in the process of filling and modifying with POM, the interfacial bonding between MWCNTs and POM is effectively enhanced through the synergistic interface improvement of the MWCNTs surface functionalization and the coupling agent, so that the tensile strength and modulus of the prepared MWCNT / POM composite material are increased by 11.3% and 13.7% respectively on the basis of the raw material POM. This technical solution has a safe and simple process, and the required equipment and environmental conditions are conventional. The prepared MWCNT / POM composite material has both antistatic and high strength, which is of great significance for promoting the localization of antistatic polyoxymethylene. DETAILED DESCRIPTION

[0028] The following is further described in detail through specific implementations, but the implementation of the present invention is not limited thereto. Unless otherwise specified, the technical means used in the following implementations are conventional means well known to those skilled in the art; the experimental methods used are all conventional methods; the materials, reagents, etc. used can all be obtained from commercial channels.

[0029] Program Overview:

[0030] A high-strength antistatic polyoxymethylene composite material comprises, by weight, 95-99.8 parts of polyoxymethylene, 0.2-5 parts of surface functionalized MWCNTs, 0.05-0.5 parts of antioxidants, 0.01-0.1 parts of formaldehyde absorbers, 0.05-0.5 parts of nucleating agents, 0.05-0.2 parts of lubricants, and 0.2-2 parts of coupling agents.

[0031] The antioxidant includes at least one of [methyl-β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] pentaerythritol ester (antioxidant 1010), triethylene glycol bis-3-(3-tert-butyl-4-hydroxy-5-toluene phenyl) acrylate (antioxidant 245), 2,4,6-tri-tert-butylphenol (antioxidant 246), 2,6-di-tert-butyl-p-cresol (antioxidant 264), 2,6-di-tert-butyl-4-ethylphenol (antioxidant DBEP), and β-(4-hydroxy-3,5-di-tert-butylphenyl) propionate (antioxidant 1076).

[0032] The formaldehyde absorbent includes at least one of sebacic acid dihydrazide, 1,3-diamino-2-propanol, dicyandiamide, melamine and triethanolamine.

[0033] The nucleating agent includes at least one of di(4-tert-butyl-benzoic acid)aluminum hydroxide (Sandostab 4030), aromatic amide compound (TMB-5), di(p-methylbenzylidene) sorbitol, MDBS, di(p-chlorobenzylidene) sorbitol, DBS (TM-2), and di(3,4-dimethylbenzylidene) sorbitol (Millad3988).

[0034] The lubricant includes at least one of paraffin, N,N'-ethylene bisstearamide, stearic acid, and butyl stearate.

[0035] The coupling agent includes at least one of γ-(methacryloyloxy)propyltrimethoxysilane, γ-glycidyloxypropyltrimethoxysilane, γ-aminopropyltriethoxysilane, tri[(dioctyloxy)phosphoryl]titanate isopropyl and diisostearoyltitanate ethylene glycol; the lubricant includes at least one of liquid paraffin, polyethylene wax, butyl stearate and polymethylphenylsiloxane.

[0036] The preparation method of surface functionalized MWCNTs (multi-walled carbon nanotubes) comprises the following steps:

[0037] S1: Add 1 mol of p-nitroaniline and 50 mL of hydrochloric acid to 1 L of deoxygenated water, heat to 90°C while stirring with a magnetic stirrer to completely dissolve the p-nitroaniline, then pass cooling water to cool the p-nitroaniline to room temperature.

[0038] S2: Dissolve 50g of sodium nitrite in 100mL of desalted water, then quickly add it to the precipitated p-nitroaniline solution, and react for 40min under continuous cooling and magnetic stirring. After the reaction is completed, filter, and the filtrate is the desired p-nitroaniline diazonium salt.

[0039] S3: Add 200g of sodium dodecyl sulfate as a surfactant to 2kg of MWCNTs, add to 4L of desalted water, and stir magnetically for 40min. Then, drop the newly prepared p-nitroaniline diazonium salt into the MWCNTs suspension, and continue to stir magnetically for 5h after the diazonium salt is added. After the reaction is completed, filter to obtain surface-functionalized MWCNTs.

[0040] S4: The surface-functionalized MWCNTs are fully rinsed with desalted water to remove residual diazonium salt, and then freeze-dried to obtain dry and dispersed surface-functionalized MWCNTs.

[0041] A method for preparing a high-strength antistatic polyoxymethylene composite material comprises the following steps:

[0042] Step 1: coating a coupling agent on the surface of polyformaldehyde pellets, and baking to obtain polyformaldehyde coated with the coupling agent;

[0043] Step 2: Mix the coupling agent-coated polyoxymethylene, antioxidant, formaldehyde absorbent, lubricant and surface-functionalized MWCNTs, and then add them into a high-speed mixer and mix them evenly to obtain a composite material raw material;

[0044] Step 3: Add the composite material raw materials mixed evenly in step 2 to the main feeding port of the twin-screw extruder, and obtain moist MWCNT / POM composite material pellets through extrusion, cooling, drawing, and granulation, and then obtain MWCNT / POM composite materials through drying; the temperatures of each section from the main feeding port of the twin-screw extruder to the die are set to 150°C, 190°C, 200°C, 205°C, 210°C, and 220°C, respectively, and the host frequency is 20 to 50 Hz.

[0045] The present invention is further described in detail below through several specific examples. In the examples, the polyoxymethylene used is M90 pellets produced by Chongqing Yuntianhua Tianju New Materials Co., Ltd., and multi-walled carbon nanotubes (purity>95%) and single-walled carbon nanotubes (purity>95%) are provided by Beijing Dekedaojin Technology Co., Ltd.

[0046] Example 1

[0047] A high-strength antistatic polyoxymethylene composite material comprises, by weight, 99 parts of polyoxymethylene, 1.0 part of surface functionalized MWCNTs, 0.4 part of an antioxidant (0.3 part of antioxidant 1010 + 0.1 part of antioxidant 245), 0.02 part of formaldehyde absorber sebacic acid dihydrazide, 0.1 part of nucleating agent di(p-methylbenzylidene) sorbitol; 0.15 part of lubricant N,N'-ethylene bisstearamide, and 1.0 part of coupling agent tri[(dioctyloxy)phosphoryl] isopropyl titanate.

[0048] A method for preparing a high-strength antistatic polyoxymethylene composite material comprises the following steps:

[0049] Step 1: coating a coupling agent on the surface of polyformaldehyde pellets, and baking to obtain polyformaldehyde coated with the coupling agent;

[0050] Step 2: Mix the coupling agent-coated polyoxymethylene, antioxidant, formaldehyde absorbent, lubricant and surface-functionalized MWCNTs, and then add them into a high-speed mixer and mix them evenly to obtain a composite material raw material;

[0051] The preparation method of surface functionalized MWCNTs comprises the following steps:

[0052] S1: Add 1 mol of p-nitroaniline and 50 mL of hydrochloric acid to 1 L of deoxygenated water, heat to 90°C while stirring with a magnetic stirrer to completely dissolve the p-nitroaniline, and then pass cooling water to cool the p-nitroaniline to room temperature;

[0053] S2: Dissolve 50g of sodium nitrite in 100mL of desalted water, then quickly add it to the precipitated p-nitroaniline solution, and react for 40min under continuous cooling and magnetic stirring; filter after the reaction, and the filtrate is the desired p-nitroaniline diazonium salt;

[0054] S3: Add 200g of sodium dodecyl sulfate as a surfactant to 2kg of MWCNTs, add to 4L of desalted water, and stir magnetically for 40min. Then, add the newly prepared p-nitroaniline diazonium salt dropwise to the MWCNTs suspension, and continue to stir magnetically for 5h after the diazonium salt is added. After the reaction is completed, filter to obtain surface-functionalized MWCNTs.

[0055] S4: The surface-functionalized MWCNTs were fully rinsed with desalted water to remove residual diazonium salt, and then freeze-dried to obtain dry dispersed MWCNTs;

[0056] Step 3: Add the composite material raw materials mixed evenly in step 2 to the main feeding port of the twin-screw extruder, and obtain moist MWCNT / POM composite material pellets through extrusion, cooling, drawing, and granulation, and then obtain MWCNT / POM composite materials through drying; the temperatures of each section from the main feeding port of the twin-screw extruder to the die are set to 150°C, 190°C, 200°C, 205°C, 210°C, and 220°C, respectively, and the host frequency is 20 to 50 Hz.

[0057] Example 2

[0058] The difference between this embodiment and embodiment 1 is that: in this embodiment, a high-strength antistatic polyformaldehyde composite material, in parts by weight, the raw materials include: 97 parts of polyformaldehyde, 3 parts of surface functionalized MWCNTs, 0.3 parts of antioxidant 1010, 0.05 parts of formaldehyde absorbent sebacic acid dihydrazide, 0.3 parts of nucleating agent di(4-tert-butyl-benzoic acid) aluminum hydroxide (Sandostab4030), 0.1 parts of lubricant N,N'-ethylene bisstearamide, and 1.5 parts of coupling agent tri[(dioctyloxy)phosphoryl]titanate isopropyl ester.

[0059] Example 3

[0060] The difference between this embodiment and embodiment 1 is that: in this embodiment, a high-strength antistatic polyformaldehyde composite material, in parts by weight, the raw materials include: 99.8 parts of polyformaldehyde, 0.2 parts of surface functionalized MWCNTs, 0.5 parts of antioxidant 1010, 0.1 parts of formaldehyde absorber sebacic acid dihydrazide, 0.5 parts of nucleating agent di(4-tert-butyl-benzoic acid) aluminum hydroxide (Sandostab4030), 0.2 parts of lubricant N,N'-ethylene bisstearamide, and 0.2 parts of coupling agent γ-(methacryloyloxy)propyltrimethoxysilane.

[0061] Example 4

[0062] The difference between this embodiment and embodiment 1 is that: in this embodiment, a high-strength antistatic polyformaldehyde composite material, in parts by weight, the raw materials include: 95 parts of polyformaldehyde, 5 parts of surface functionalized MWCNTs, 0.05 parts of antioxidant 1010, 0.01 parts of formaldehyde absorbent sebacic acid dihydrazide, 0.05 parts of nucleating agent di(4-tert-butyl-benzoic acid) aluminum hydroxide (Sandostab4030), 0.05 parts of lubricant stearic acid, and 1.0 parts of coupling agent γ-glycidyloxypropyltrimethoxysilane.

[0063] Comparative Example 1

[0064] This comparative example is basically the same as Example 2, except that the MWCNTs used in step 2 of the composite material preparation method are not surface functionalized, that is, there is no step of preparing surface functionalized MWCNTs in the composite material preparation process, and the rest is the same as Example 2. The properties of the MWCNT / POM composite material prepared in this comparative example are shown in Table 2. The mechanical and electrical properties of the MWCNT / POM composite material prepared in this comparative example are significantly lower than those of the composite material prepared in Example 2 using MWCNTs surface functionalized with p-nitroaniline diazonium salt. Defects are formed on the surface of MWCNTs that have been surface functionalized, hydrophilic functional groups are grafted, the interfacial interaction with the POM matrix is ​​greatly enhanced, and the dispersibility in the matrix is ​​greatly enhanced, thereby significantly improving the mechanical and electrical properties of the composite material.

[0065] Comparative Example 2

[0066] This comparative example is basically the same as Example 2, except that: a mixed acid of concentrated sulfuric acid / concentrated nitric acid with a volume ratio of 3:1 is used instead of p-nitroaniline diazonium salt to perform surface functionalization treatment on MWCNTs to obtain MWCNTs with surface grafted carboxyl groups. Others are the same as Example 2. The properties of the MWCNT / POM composite material prepared in this comparative example are shown in Table 2. The analysis and test results show that the main mechanical properties and electrical properties of the composite material prepared in this comparative example are lower than those of Example 2.

[0067] Comparative Example 3

[0068] This comparative example is basically the same as Example 2, except that: the preparation method of surface functionalized MWCNTs is different, wherein in step S1, MWCNTs are oxidized with concentrated sulfuric acid / concentrated nitric acid in a volume ratio of 3:1 to obtain MWCNTs with surface grafted carboxyl groups; thionyl chloride is used to react with carboxylated MWCNTs in S2; triethylenetetramine is further used to graft with MWCNTs in S3 to finally obtain amine functionalized MWCNTs. Others are the same as Example 2. The properties of the MWCNT / POM composite material prepared in this comparative example are shown in Table 2. The analysis and test results show that the main mechanical properties and electrical properties of the composite material prepared in this comparative example are lower than those in Example 2.

[0069] Comparative Example 4

[0070] This comparative example is basically the same as Example 2, except that the carbon nanotubes used in step 2 are surface functionalized single-walled carbon nanotubes (SWCNTs). The preparation method and other steps of surface functionalized SWCNTs are the same as those in Example 2. The properties of the SWCNT / POM composite material prepared in this comparative example are shown in Table 2. The analysis and test results show that the mechanical properties and electrical properties of the SWCNT / POM composite material are significantly lower than those of the MWCNT / POM prepared in Example 2.

[0071] Comparative Example 5

[0072] This comparative example is basically the same as Example 2, except that: the raw materials do not include a coupling agent, therefore, there is no step one in the preparation method of the MWCNT / POM composite material, and the polyoxymethylene used in step two is not coated with a coupling agent. The rest is the same as Example 2. The properties of the SWCNT / POM composite material prepared in this comparative example are shown in Table 2. The analysis and test results show that the main mechanical properties and electrical properties of the composite material prepared in this comparative example are significantly lower than those in Example 2. On the basis that both MWCNTs and POM have excellent mechanical properties, the mechanical properties of the MWCNT / POM composite material depend on the interfacial bonding strength of the two phases, and the electrical properties depend on the content and distribution of MWCNTs in the POM matrix. Functionalization treatment of the surface of MWCNTs can effectively improve the interfacial effect of the two phases and its dispersibility in the POM matrix, but without the synergistic effect of the coupling agent, the interfacial bonding improvement effect is not significant.

[0073] The electrical properties and mechanical properties of the MWCNT / POM composite materials prepared in the above embodiments and comparative examples were tested. The experiment was repeated three times for each group. The test methods and test results are shown in Tables 1 and 2.

[0074] Table 1 Electrical and mechanical properties of the MWCNT / POM composites prepared in Example.

[0075]

[0076] Table 2 Electrical and mechanical properties of MWCNT / POM and SWCNT / POM composites prepared in comparative example.

[0077]

[0078] The above is only an embodiment of the present invention, and the common knowledge such as the known specific technical solutions and / or characteristics in the solution is not described in detail here. It should be pointed out that for those skilled in the art, without departing from the technical solution of the present invention, several modifications and improvements can be made, which should also be regarded as the protection scope of the present invention, and these will not affect the effect of the implementation of the present invention and the practicality of the patent. The scope of protection required by this application shall be based on the content of its claims, and the specific implementation methods and other records in the specification can be used to interpret the content of the claims.

Claims

1. A high-strength antistatic polyoxymethylene composite material, characterized in that: The invention comprises, by weight, 95 to 99.8 parts of polyoxymethylene, 0.2 to 5 parts of surface functionalized MWCNTs, 0.05 to 0.5 parts of antioxidant, 0.01 to 0.1 parts of formaldehyde absorbent, 0.05 to 0.5 parts of nucleating agent, 0.05 to 0.2 parts of lubricant and 0.2 to 2 parts of coupling agent.

2. The high-strength antistatic polyoxymethylene composite material according to claim 1, characterized in that: The weight proportions of the raw materials are 97-99 parts of polyoxymethylene, 1-3 parts of surface functionalized MWCNTs, 0.4 parts of antioxidant, 0.05 parts of formaldehyde absorbent, 0.3 parts of nucleating agent, 0.15 parts of lubricant and 1.0 parts of coupling agent.

3. The high-strength antistatic polyoxymethylene composite material according to claim 2, characterized in that: The modification method of the surface functionalized MWCNTs is: grafting p-nitrophenyl on the surface of multi-walled carbon nanotubes.

4. The high-strength antistatic polyoxymethylene composite material according to claim 3, characterized in that: The modification method of the surface functionalized MWCNTs comprises the following steps: S1: Add p-nitroaniline and hydrochloric acid to deoxygenated water, stir to dissolve and then cool; S2: dissolving sodium nitrite in desalted water, then quickly adding it to the p-nitroaniline precipitate, and reacting under stirring; filtering after the reaction is completed, and the filtrate is p-nitroaniline diazonium salt; S3: adding a surfactant to the MWCNTs, adding the mixture to desalted water, stirring, and adding p-nitroaniline diazonium salt; filtering after the reaction is completed to obtain surface functionalized MWCNTs; S4: washing the surface functionalized MWCNTs with desalted water to remove residual diazonium salt, and then freeze-drying to obtain dry and dispersed surface functionalized MWCNTs.

5. The high-strength antistatic polyoxymethylene composite material according to claim 4, characterized in that: The antioxidant includes at least one of [methyl-β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] pentaerythritol ester, triethylene glycol bis-3-(3-tert-butyl-4-hydroxy-5-toluene phenyl) acrylate, 2,4,6-tri-tert-butylphenol, 2,6-di-tert-butyl-p-cresol, 2,6-di-tert-butyl-4-ethylphenol, and β-(4-hydroxy-3,5-di-tert-butylphenyl) propionate.

6. The high-strength antistatic polyoxymethylene composite material according to claim 5, characterized in that: The formaldehyde absorbent includes at least one of sebacic acid dihydrazide, 1,3-diamino-2-propanol, dicyandiamide, melamine and triethanolamine; the nucleating agent includes at least one of di(4-tert-butyl-benzoic acid)aluminum hydroxide, aromatic amide compounds, di(p-methylbenzylidene)sorbitol, MDBS, di(p-chlorobenzylidene)sorbitol, DBS and di(3,4-dimethylbenzylidene)sorbitol.

7. The high-strength antistatic polyoxymethylene composite material according to claim 6, characterized in that: The lubricant includes at least one of paraffin, N,N'-ethylene bisstearamide, stearic acid, and butyl stearate; the coupling agent includes at least one of γ-(methacryloyloxy)propyl trimethoxysilane, γ-glycidyloxypropyl trimethoxysilane, γ-aminopropyl triethoxysilane, tris[(dioctyloxy)phosphoryl] isopropyl titanate, and diisostearoyl titanate; the lubricant includes at least one of liquid paraffin, polyethylene wax, butyl stearate, and polymethylphenylsiloxane.

8. The method for preparing a high-strength antistatic polyoxymethylene composite material according to any one of claims 1 to 7, characterized in that: The steps include: Step 1: coating a coupling agent on the surface of polyformaldehyde pellets, and baking to obtain polyformaldehyde coated with the coupling agent; Step 2: Mix the coupling agent-coated polyoxymethylene, antioxidant, formaldehyde absorbent, lubricant and surface-functionalized MWCNTs, and then add them into a high-speed mixer and mix them evenly to obtain a composite material raw material; Step 3: Extruding and granulating the composite material uniformly mixed in step 2 to obtain a MWCNT / POM composite material.

9. The method for preparing a high-strength antistatic polyoxymethylene composite material according to claim 8, characterized in that: In step three, the composite material raw material is added to the main feed port of the twin-screw extruder, and wet MWCNT / POM composite material pellets are obtained through extrusion, cooling, drawing and granulation, and then the MWCNT / POM composite material is obtained through drying.

10. The method for preparing a high-strength antistatic polyoxymethylene composite material according to claim 9, characterized in that: In step three, the temperatures of each section from the main feed port to the die of the twin-screw extruder are set to 150°C, 190°C, 200°C, 205°C, 210°C, and 220°C, respectively, and the main engine frequency is 20-50Hz.